EFEKTIVITAS MYOFASCIAL RELEASE DAN STRENGTHENING EXERCISE TERHADAP NYERI DAN PENINGKATAN AKTIVITAS FUNGSIONAL PADA KONDISI TENSION HEADACHE - Nita Ardiani; Agus Widodo; Farid Rahman (Jurnal Fisioterapi dan Rehabilitasi, 2018)
Background:The impact of high-end student load on final project would triggerphysical stress that such as tension headache. This was influenced by ergonomicposition and neck muscle work at low level consentric. The purpose of thisresearch is knowing effect of myofascial release and strengthening exercise todecrease pain and improve functional activity for tension headache condition.Methods: This study was quasy experiment two group with control, conducted onJanuary 6 – Februari 3 2018. Sampling method by incidental sampling approach16 students were conducted for this study, divided into 2 groups. The treatmentgroup was (myofascial release and strengthening exercise) and performed painand functional measurements by using VAS (Visual Analogue Scale). dataanalysis used shapiro wilk test, leuvene test, paired sample t-test, and independentsample t-testResult: The influence of myofascial release and strengthening exercise on thedecrease of pain with the result p = 0.000, while the increase of functional activitythat is p = 0.000 which means the influence of (+) to the increase of functionalactivity. The existence of different treatment groups (myofascial release andstrenthening exercise) and the control group (strecthing) with p = 0.001.Conclusion: There was influence myofascial release and strengthening exerciseon the reduction of pain in the condition of tension headache.